A method to evaluate metal enrichment in marine sediments. - Lizano, Omar G. (2012)
In order to evaluate metal enrichment in sediments , a method is proposed and tested in Bahia Culebra and the Golfo de Nicoya, Costa Rica through the normalization of the elements against aluminum, and by linear regression of the logarithm of the concentrations of different elements respect to aluminum. The distributions of the elements manganese, and strontium of Bahía Culebra did not satisfy the tests of normalization and linear regression, indicating a nonnatural distribution or enrichment of these elements in this region. In the Golfo de Nicoya the elements copper , zinc , rubidium and the strontium did not satisfy the test of normality or the linear regression with respect to aluminum, indicating a possible enrichment of these elements. The majority of the concentrations of the elements in two sample sites, with the exception of chromium, are within the natural ranges in rocks or clays of marine sediments, and within the concentration ranges of other studies done in these same regions. Chromium has average values beyond the natural concentrations, the values of some samples in the Golfo de Nicoya are up to 10 times greater than the concentration value of a typical bay with high contamination of this element.